VII Shakespeare. Issue 1 (18th July 2020) - Young, Jennifer; Smith, Peter J; Parsons, Elinor; Tarantino, Elisabetta; Stelzer, Emanuel; Bell, Shirley; Haworth, Ben; Lim, Vanessa; O'Brien, Sheilagh Ilona; Wilkinson, Kate
Abstract: This chapter has four sections: 1. Editions and Textual Studies; 2. Shakespeare in the Theatre; 3. Shakespeare on Screen; 4. Criticism. Section 1 is by Jennifer Young; section 2 is by Peter J. Smith; section 3 is by Elinor Parsons; section 4(a) is by Elisabetta Tarantino; section 4(b) is by Emanuel Stelzer; section 4(c) is by Shirley Bell; section 4(d) is by Ben Haworth; section 4(e) is by Vanessa Lim; section 4(f) is by Sheilagh Ilona O'Brien; section 4(g) is by Kate Wilkinson.